The effect of exchange rate volatility on bond market development in emerging markets - Mokgotloa, Refiloe (Graduate School of Business (GSB), 2025)
This paper examines the effect of exchange rate volatility on bond market development in 13 emerging markets for the period 2000 to 2020 as well as whether the investor base moderates the relationship between exchange rate volatility and bond market development for the period 2004 to 2020. Using a panel data set and the feasible generalized least squares (FGLS) method we find that exchange rate volatility has a negative and statistically significant relationship to bond market development. This finding is consistent with existing literature. We also find that the investor base has a negative and statistically significant relationship to bond market development and that in the emerging markets where there is a higher level of foreign investors and exchange rate volatility there are higher levels of bond market development. Policymakers should therefore implement policies that manage and reduce exchange rate volatility to support bond market development. These can include ensuring that central banks hold healthy levels of foreign exchange reserves to be able to support their currency in a crisis. Policymakers in unrated countries should also engage with reputable external credit rating agencies for foreign investors to have externally validated information on the sovereign's ability to meet its obligations and therefore increase the attractiveness of the local bond market to foreign investors.